Mesenchymal stem cells for cardiac repair: are the actors ready for the clinical scenario? - Roura, Santiago (Stem Cell Res Ther, 2017)
For years, sufficient progress has been made in treating heart failure following myocardial infarction; however, the social and economic burdens and the costs to world health systems remain high. Moreover, treatment advances have not resolved the underlying problem of functional heart tissue loss. In this field of research, for years we have actively explored innovative biotherapies for cardiac repair. Here, we present a general, critical overview of our experience in using mesenchymal stem cells, derived from cardiac adipose tissue and umbilical cord blood, in a variety of cell therapy and tissue engineering approaches. We also include the latest advances and future challenges, including good manufacturing practice and regulatory issues. Finally, we evaluate whether recent approaches hold potential for reliable translation to clinical trials.